Non-ownership business models in the manufacturing industry: Uncertainty-exploiting versus uncertainty-mitigating designs and the role of context factors - Maximilian Bock; Martin Wiener; Carol Saunders (Electronic Markets, 2023)
With the emergence of the Industrial Internet of Things, a growing number of manufacturing firms has started to adopt non-ownership business models (NOBMs). NOBM providers maintain ownership of offered machinery and sell only the machine use and/or performance as a service to their clients. While the adoption of NOBMs is found to be associated with novel business opportunities related to client-side uncertainties, it is also found to result in a considerable increase in provider-side uncertainties. Drawing on a multiple-case study with three leading manufacturers, we find notable differences in terms of NOBM designs, ranging from a primary focus on exploiting client-side uncertainties to a primary focus on mitigating provider-side uncertainties. Moreover, our study uncovers four context factors that help explain key differences in NOBM designs. In particular, we identify two machine attributes (human dependency and energy efficiency) and two market attributes (average client size and antitrust regulations) that "push" providers toward either uncertainty-exploiting or uncertainty-mitigating NOBM designs. Theoretical and practical implications are discussed.
Keywords: L22; L64; L86; 620; Non-ownership business models (NOBMs); NOBM designs; Uncertainty exploitation vs. mitigation; Context factors; Manufacturing industry; Multiple-case study